Modulation of mechanical interactions by local piezoelectric effects - Brown, C; Boyd, J; Palmer, A; Phillips, M; Couture, C; Rivard, M; Hulley, P; Price, A; Ruediger, A; Legare, F; Carr, A (Wiley, 2016)
Piezoelectricity is a well-established property of biological materials, yet its functional role has remained unclear. Here, we demonstrate a mechanical effect of piezoelectric domains resulting from collagen fibril organisation, and describe its role in tissue function and application to material design. Using a combination of scanning probe and nonlinear optical microscopy, we observed a hierarchical structuring of piezoelectric domains in collagen-rich tissues, and explored their mechanical effects in silico. Local electrostatic attraction and repulsion due to shear piezoelectricity in these domains modulate fibril interactions from the tens of nanometre (single fibril interactions) to the tens of micron (fibre interactions) level, analogous to modulated friction effects. The manipulation of domain size and organisation thus provides a capacity to tune energy storage, dissipation, stiffness and damage resistance.